The Role of Social Capital in Management of Baros Mangrove Conservation Area Yogyakarta - Setyaningrum, Agustina; Widyaputra, Primanda Kiky; Febriarta, Erik; Putro, Sutanto Trijuni (Universitas Muhammadiyah Surakarta, 2022)
The coastal area in Baros is frequently flooded and influenced by tides during the high tide. The mangrove ecosystem in this area has decrease severely. As the result, the coastal area is unprotected, and several negative impacts received by the coastal area. Inadequate concern coming from government, negative impact of natural disaster, as well as the high concern of local community leads to the establishment of mangrove replant program and mangrove eco-tourism establishment. Baros Youth Group which concern in environmental protection and management in Baros Coastal Area. The activities facing many challenges and obstacles. Therefore, collaboration with government, community, private party and academics leads to the success of Baros Youth Group to overcome the challenges and obstacle. This study was aimed for understanding the role of social capital in the management of Baros Mangrove conservation area. The study consists of four stages, which are observation, data collection, data processing and analysis. Data collecting process was done in accordance with the parameters of social capital which are consists of norms, trust and social network. The samples were taken by purposive method. The results of this study shown that the norms in society encourage them to respect each other and not disturb each other, the trust level is depended on the activities of society member, and the social network is high indicated by the increasing of community participation in planting mangrove seedlings.